Peningkatan Motorik Kasar Anak Melalui Tari Pendet untuk Anak Usia 5-6 Tahun (Studi Kasus) di Wilayah Abiantubuh Utara - Gusti Ayu Trisni Perdani; I Made Suwasa Astawa; Baik Nilawati Astini; Nurhasanah Nurhasanah (Indonesian Publication Center, 2022)
The background of this research is the low gross motor skills, especially in dancing activities in children aged 5-6 years in the North Abianbuh Region. This study aims to find out whether the implementation of the Pendet Dance can improve children's gross motor skills in the North Abiandinding region in 2020. The type of research used is descriptive qualitative research. The research subjects were 3 children. The data collection method used is the method of observation, interviews, and documentation. Data analysis used is descriptive qualitative analysis. The results of the study show that the Improvement of Children's Gross Motor through Pendet Dance for Children Aged 5-6 years (case study) in the North Abiandinding region in 2020 can be said to be developing according to expectations (BSH). This can be seen from the research instrument, namely 10 Pendet dance movements sequentially through 4 research stages. 1st stage the child's average value reaches 33.3% 2nd stage the child's average value reaches 66.6% to 70% 3rd stage the child's average value reaches 80%, up to 83.3% and the 4th stage the average value -the average child reaches 100%. From this study it can be concluded that the application of the Pendet Dance can improve children's gross motor skills in the North Abiandinding region in 2020.